Azithromycin paradox in the treatment of cystic fibrosis airway disease. (September 2010) - Sibley, Christopher; Grinwis, Margot E; Rabin, Harvey R; Surette, Michael G
Evaluation of: Saiman L, Anstead M, Mayer-Hamblett N et al. : Effect of azithromycin on pulmonary function in patients with cystic fibrosis uninfected with Pseudomonas aeruginosa : a randomized controlled trial. JAMA 303(17), 1707–1715 (2010). Chronic airway infection and inflammation are hallmarks of cystic fibrosis (CF). Disease progression can be described as chronic inflammation punctuated by acute exacerbations with overt immunological responses. Macrolide antibiotics, which have both immunomodulatory and antibacterial activities, have been shown to be beneficial in the management of CF airway disease, although the mechanism of action is unknown. It is also unclear whether all patients, particularly those not colonized with Pseudomonas aeruginosa, benefit from this treatment. In this article, Saiman et al. examine the effects of azithromycin on lung function in pediatric and adolescent CF patients who are not colonized with P. aeruginosa . The data indicate beneficial effects of azithromycin treatment and suggest the mechanisms of action of azithromycin is at least partially independent of P. aeruginosa .